Tingkat Ketersediaan Obat di Puskesmas Kota Selatan dan Puskesmas Piloloda’a Tahun 2024 - Muhammad Ridho Jasin; Madania Madania; Teti Sutriyati Tuloli (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2026)
Drug availability at community health centers is an important indicator of health service quality. Drug shortages or excesses may affect service effectiveness and budget efficiency. This study aimed to determine the level of drug availability at the South City Community Health Center and the Piloloda'a Community Health Center in 2024 based on compliance with the formulary, demand, receipt, and drug availability categories. This study used a descriptive analytical method with a cross-sectional approach. Data were obtained retrospectively from the 2024 Drug Use Report and Request Sheet (LPLPO). Data analysis was conducted by calculating the percentage of compliance with the formulary, demand, and receipt, and by determining drug availability levels using the Indonesian Ministry of Health (2010) formula and the classification of Carolien et al. (2017). The results showed that formulary compliance was 82% at the South City Community Health Center and 67% at the Piloloda'a Community Health Center, both below the 95% standard. Drug demand compliance scores were 151% and 199%, exceeding the 100–120% standard, while drug receipt compliance scores were 71% and 56%, below the 100% standard. Drug availability categories varied from adequate and insufficient to excess stock, with most drug items classified as insufficient stock. In conclusion, drug management at both community health centers has not been fully optimal. Improved coordination between community health centers and pharmaceutical facilities is needed to maintain stable drug availability and support service needs.